The Effect of Banking Services In achieving Copetetive Advantage – A Case study: Omdurman National Bank, 2017- 2021 – - Mursal, Mona Elneel Mostafa; Mohammed, Hanan Osman Amasaib (Journal of Economic, Administrative and Legal Sciences, 2022)
The aim of the research is to identify the concept of banking services and its various dimensions, to identify the concept of competitive advantage and ways to achieve it, and to study the impact of banking services on achieving competitive advantage in Sudanese banks, through the main hypothesis test: There is a statistically significant relationship between banking services (with its three dimensions) And the competitive advantage in Omdurman National Bank. The questionnaire was used to collect data from the study population through a simple random sample of employees in Omdurman National Bank with a number of (36), and the valid questionnaires for analysis were (34). The study reached a number of results, the most important of which is the existence of a correlation between banking services with its three components (local banking services, electronic banking services, external banking services) and competitive advantage, Where the correlation coefficient between the three types of banking services, respectively, with the competitive advantage was (0.626, 0.540, 0.682), which indicates a strong positive correlation. The research was recommended a number of recommendations to take into account the development of banking services to keep abreast of developments In the global banking market.
Keywords: Banking Services; Competitive Advantage; Omdurman National Bank